1998
DOI: 10.1093/molehr/4.10.946
|View full text |Cite
|
Sign up to set email alerts
|

Secretory leukocyte protease inhibitor (SLP) concentrations in seminal plasma: SLPI restores sperm motility reduced by elastase

Abstract: In this study, we quantified secretory leukocyte protease inhibitor (SLPI) and elastase in ejaculates from normal donors and infertile patients with or without leukospermia and investigated the effect of SLPI on sperm motility reduced by elastase. Western blot analysis revealed that SLPI protein was detected in the seminal plasma. The SLPI titre in the seminal plasma with leukospermia was lower than that in the seminal plasma without leukospermia and in the seminal plasma of fertile donors. The elastase concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
2
18
1
1
Order By: Relevance
“…There was no significant correlation between elastase and SLPI levels in seminal plasma. Our findings differ from the results of Moriyama et al [8], who demonstrated a statistically significant negative correlation between elastase and SLPI concentrations in seminal plasma. The following facts may explain the difference between their data and ours.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There was no significant correlation between elastase and SLPI levels in seminal plasma. Our findings differ from the results of Moriyama et al [8], who demonstrated a statistically significant negative correlation between elastase and SLPI concentrations in seminal plasma. The following facts may explain the difference between their data and ours.…”
Section: Discussioncontrasting
confidence: 99%
“…Since semen leukocytes, but not immature germ cells, secrete granulocyte elastase, the measurement of granulocyte elastase by an ELISA would be an objective and convenient method for estimating the concentrations of semen leukocytes. Moriyama et al [8] demonstrated that the incubation of spermatozoa with recombinant elastase reduced sperm motility. However, in vivo, endogenous inhibitors, including secretory leukocyte protease inhibitor (SLPI) and a l -protease inhibitor (a l -PI), in seminal plasma are thought to protect spermatozoa from attack by elastase.…”
mentioning
confidence: 99%
“…The concentrations of SLPI tested were within the physiological levels of SLPI expressed constitutively in both the female and male urogenital tracts. 14,39 Further, the concentrations of SLPI and the degree of bactericidal activity were comparable to that reported for the gram-negative bacteria E. coli and S. typhimurium , 18,19 although the bactericidal activity in those studies required a four-fold longer incubation period suggesting that SPLI may be more active against gonococci. Two other innate immune antimicrobial peptides, HE2α and cathelicidin LL-37, which are expressed to greater degrees in the male compared with the female urogenital tract have been reported to exhibit bactericidal activity against gonococci, 40,41 although the underlying mechanisms of their antimicrobial activities have not been not identified.…”
Section: Discussionsupporting
confidence: 74%
“…20 Pulmonary monocytes from patients with cystic fibrosis express proteinase 3, 52 and the levels of proteinase 3 activity are greater than those of elastase in the sputum from patients with cystic fibrosis who have chronic lung infections. 53 SLPI is assumed to play an important role in the protection against the leukocyte proteases, elastase, and cathepsin G and in the mucosa at various sites-eg, in airway fluid, 54 semen, 55 and keratinocytes. 56 The presence of SLPI in these tissues will not interfere with proteinase 3-mediated cleavage of hCAP-18, as would have been the case if elastase or cathepsin G cleaved hCAP-18.…”
Section: Discussionmentioning
confidence: 99%